Igreja e missão : religiosos e ação política no Brasil - Neris, Wheriston Silva (2014)
This work has for subject the examination of concrete mediations through which certain members of the clergy were conducted to live theirs work as directly political and socially engaged, taking as analysis s reference an empirical space represented by Maranhão, from the second half of the twentieth century. It investigates, in particular, the practical contexts, the institutional settings and both individual and collective logic that favored the transgression of rules and transits between spheres of activity, promoted by certain agents who challenged the definitions and legitimate limits of Catholic religious action. The choice of an institutional component distant to Rome and centers of national decision of the Catholic Church served the purpose of analyzing, below a located, procedural and microscopic perspective, the concrete and contingent arrangements of transaction between religious and political phenomena, noting the historical, social and institutional settings, including individual itineraries and discourses produced by a small fraction of the ecclesial métier that defied most noticeably those boundaries. The advancement in the reconstitution of the processes of institutional transformation of the Church through this small component objectified then led to identify three important dimensions of analysis to make intelligible the politicization of religious engagement of priests in theirs context of possibility. In the first, to reconstitute the genesis of this peripheral component of the Church, it was analyzed how this church was continually being shaped by social relations established in its territory, the evolution of effective and its institutional framework, as well as its growing links to new Catholic guidelines for pastoral, doctrinal and / or liturgical matter (first chapter). Moreover, analyzing various factors of renewal institutional of Catholicism in international, national and regional level, the second level of observation places the accent either on the effects of redefining the imposed boundaries that separate the clergy from the laity over the management of religious property, much about the conditions that led the church to become a powerful moral and organizational supporter of mobilizations and social movements in Maranhão (second chapter). On a third level of analysis, this work focuses on the exploration of the various effects of closer ties of the Catholic Church of Maranhão to the transnational networks, especially through the denationalization of clerical effective charge of taking care of their reproduction (corresponding to the third and fourth chapters). In particular, in this plan explores the effects of globalization on the development of new forms of exercising religious role in missionary territory in question, as the understanding of their mission as a place of interpenetration stories, of identity restoration and reinvention established practice. This study thus highlights the diversity of conditions by which some religious they felt allowed both assume the role of spokesmen and interpreters of their professional environment, as to play the role of intermediaries primordial of discontent of the population and values and ideals that transcended his metier.